Pengembangan Prototipe Pencatatan Operasi Katarak Berbasis Website - Monalisa Nasrul (Unram Medical Journal, 2022)
West Nusa Tenggara province ranks the second as the highest province with blindness due to cataract in people above 50 years old. Although blindness from cataract is preventable, without well-organized and accurate cataract surgical registry, actions for prevention of blindness will not be optimized. Until now, there is no single online cataract surgical registry in Indonesia that results in difficulty in retrieving cataract surgical rate and outcome data. The study aims to develop a website-based cataract surgery registry to collect pre, during and post cataract surgery in West Nusa Tenggara province followed by trials by health workers in Rumah Sakit Universitas Mataram to perfect the application before daily use. They shoud answers questions from questionnaire provided to measure their perceptions of the application. The application named Register Operasi Katarak NTB (ROKANTB) can be operated in windows, chrome or mac operating systems. The questionnaire shows good perception among health workers for application design, easy to operate, practicality, amount of time needed to fill the form, retrieving data and usefulness of the application as cataract surgery registry. ROKANTB application is a practical and useful tool to record and present cataract surgery data online from many healthcare facilities that may be useful to analize and evaluate our local and national cataract surgery program and strategies.